Współczesne ujęcia kategorii rodzaju gramatycznego w polszczyźnie a praktyka (glotto)dydaktyczna – wprowadzenie - Seretny, Anna; Stefańczyk, Wiesław Tomasz (Postscriptum Polonistyczne, 2020)
In contemporary Polish linguistics, there are two approaches to determining grammatical gender classes: the traditional and the contemporar formal. According to the traditional concept, derived from the classical school, the nominative case is the basis for the division into gender classes. In modern Polish language, the traditional approach distinguishes the following classes: masculine, feminine, and neutral and in the plural form there is also the masculinepersonal and nonmasculinepersonal. On the other hand, in the contemporary approach the basis for division into gender classes is the accusative case, and less frequently, the genitive case. In didactic practice however, and especially in teaching Polish as a foreign language, the traditional approach is applied as it is the most transparent, understandable and accessible to learners.